Congenital inferior vena cava anomalies: a review of findings at multidetector computed tomography and magnetic resonance imaging - Yang,Catherine (2013)
Inferior vena cava anomalies are rare, occurring in up to 8.7% of the population, as left renal vein anomalies are considered. The inferior vena cava develops from the sixth to the eighth gestational weeks, originating from three paired embryonic veins, namely the subcardinal, supracardinal and postcardinal veins. This complex ontogenesis of the inferior vena cava, with multiple anastomoses between the pairs of embryonic veins, leads to a number of anatomic variations in the venous return from the abdomen and lower limbs. Some of such variations have significant clinical and surgical implications related to other cardiovascular anomalies and in some cases associated with venous thrombosis of lower limbs, particularly in young adults. The authors reviewed images of ten patients with inferior vena cava anomalies, three of them with deep venous thrombosis. The authors highlight the major findings of inferior vena cava anomalies at multidetector computed tomography and magnetic resonance imaging, correlating them the embryonic development and demonstrating the main alternative pathways for venous drainage. The knowledge on the inferior vena cava anomalies is critical in the assessment of abdominal images to avoid misdiagnosis and to indicate the possibility of associated anomalies, besides clinical and surgical implications.